ICT Integrated Teaching: An Interpretive Inquiry of Teachers and Students' Perceptions on ICT based Teaching - Mishra, Nirmal Raj (Researcher: A Research Journal of Culture and Society, 2020)
ICT based teaching is the most popular fashion of today's higher education in the world. Most of the teachers and students tried to habituate in ICT tools for their teaching and learning. Due to this fact scenario, I focused on to explore the perception of teachers and students towards ICT as teaching- learning tools. It has used the qualitative approach where phenomenology as the research method to explore the realities. The teachers and students were selected through the purposive sampling. The focus group discussion and in-depth interview were conducted with the selected informants to reach the rich and depth information. The major finding is that the teachers and students were highly positive to use the ICT tools in higher education teaching. It helped to create the motivating and entertaining classroom. It also facilitated in self-learning for teachers and students. It supported to the teachers and students to develop the collaborative learning culture, where they easily promoted the supported culture.